2016
DOI: 10.1017/s204579601600086x
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drug exposure and risk of myocardial infarction

Abstract: This Section of Epidemiology and Psychiatric Sciences appears in each issue of the Journal to stress the role of the epidemiological approach to promote advances in the field of clinical psychopharmacology, with a particular attention to controversial findings. The ultimate aims are to help develop a more critical attitude towards the results of research studies published in the international literature, to promote original research projects with higher methodological standards, and to implement the most relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“… 17 IHD is one of the side effects found to be linked to the use of antipsychotics in the general population. 18 , 19 In vivo and in vitro pharmacological studies suggested that the link between antipsychotics and cardiovascular side events is possibly due to the metabolic side effects of antipsychotics, 20 blockade of dopamine type 3 receptors, 21 defect in cardiovascular and immunological factors such as brain derived neurotrophic factor (BDNF) and platelet derived growth factor receptor (PDGFR)-beta, 22 altered cardiac mitochondrial oxygen consumption, 23 or immunosuppression and leukocyte accumulation in the arterial wall. 24 However, this link has not been epidemiologically confirmed.…”
Section: Introductionmentioning
confidence: 99%
“… 17 IHD is one of the side effects found to be linked to the use of antipsychotics in the general population. 18 , 19 In vivo and in vitro pharmacological studies suggested that the link between antipsychotics and cardiovascular side events is possibly due to the metabolic side effects of antipsychotics, 20 blockade of dopamine type 3 receptors, 21 defect in cardiovascular and immunological factors such as brain derived neurotrophic factor (BDNF) and platelet derived growth factor receptor (PDGFR)-beta, 22 altered cardiac mitochondrial oxygen consumption, 23 or immunosuppression and leukocyte accumulation in the arterial wall. 24 However, this link has not been epidemiologically confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic medications commonly prescribed for patients with a variety of mental disorders such as schizophrenia, bipolar disorder, and dementia are generally believed to entail a heightened risk of acute ischemic heart disease (IHD) [ 1 ]. However, meta-analyses have reported conflicting results on this association [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study of safety and tolerability outcomes associated with exposure to psychotropic medicines remains a challenging issue. While for efficacy outcomes it is widely accepted that randomised controlled trials (RCTs) represent the most reliable and appropriate reference standard, for safety and tolerability outcomes individual RCTs may not provide satisfactory information (Barbui et al ., 2017 a ). This is especially the case for psychotropic medicines: for uncommon or rare safety outcomes, RCTs are usually underpowered to establish associations; for unexpected safety outcomes, RCTs may not have planned to systematically collect information on that outcome; for safety outcomes not occurring immediately after the intervention is provided, RTCs may be too short in duration.…”
mentioning
confidence: 99%